Sveti Toma u enciklici Fides et ratio - Bonino, Serge-Thomas (Array, 2019)
The paragraphs contained in the encyclical Fides et Ratio which are explicitly devoted to Saint Thomas Aquinas comprise a condensed summation, or rather synthesis of the entire encyclical. These paragraphs incorporate the main themes which are expounded in other sections of the encyclical (philosophy opened to faith, theology mindful of philosophy, etc.) Encyclical teachings on the role of tradition in intellectual life justifies the constant recommendations of the Church regarding the favoured teachings of Saint Thomas, as in philosophy, so too in theology.